2019
DOI: 10.1186/s12913-019-4137-7
|View full text |Cite
|
Sign up to set email alerts
|

“The number of clients is increasing but the supplies are reducing”: provider strategies for responding to chronic antiretroviral (ARV) medicines stock-outs in resource-limited settings: a qualitative study from Uganda

Abstract: Background Despite the increasing frequency of ARV medicines stock-outs in Sub-Saharan Africa, there is little research inquiring into the mitigation strategies devised by frontline health facilities. Many previous studies have focused on ‘upstream’ or national-level drivers of ARVs stock-outs with less empirical attention devoted ‘down-stream’ or at the facility-level. The objective of this study was to examine the strategies devised by health facilities in Uganda to respond to the chronic stock-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 42 publications
2
39
1
Order By: Relevance
“…This low rate could be attributed to, poor drug procurement and supply management systems, resulting from inappropriate forecasting and quantification at facility level. This is further compounded by the implementation of the 'test and treat' policy in Uganda in 2017 that recommended all people tested HIV-positive to start treatment immediately leading to increase in ART enrolment [10,22]. Despite the introduction of a web-based ARV ordering system, there still remains a need to train of dispensers and pharmacists at health facilities in the use of this system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This low rate could be attributed to, poor drug procurement and supply management systems, resulting from inappropriate forecasting and quantification at facility level. This is further compounded by the implementation of the 'test and treat' policy in Uganda in 2017 that recommended all people tested HIV-positive to start treatment immediately leading to increase in ART enrolment [10,22]. Despite the introduction of a web-based ARV ordering system, there still remains a need to train of dispensers and pharmacists at health facilities in the use of this system.…”
Section: Discussionmentioning
confidence: 99%
“…Zakumupa et al in their appraisal of the ARV supply chain system in Uganda [22,23], observed that inaccurate ART medicine quantification, untimely ARV orders,over stocking of select ARVs, maldistribution of drugs contributed to stock-outs of drugs at facilities. In addition, Windisch noted that poor quality and inefficiencies in the drug supply chain management in Uganda was caused by parallel processes and information systems amplified by inadequacies at all levels of the health system, including the areas of financing, governance, human resources and information [23].…”
Section: Discussionmentioning
confidence: 99%
“…Face-to face interviews were conducted in participants' offices within the health facilities between April and June 2019. The interviews were conducted by the first author who holds a PhD in health systems and has an academic background in the social sciences and an expertise in qualitative research [22], [25]. The first author was assisted by three Research Assistants (RAs) experienced in qualitative health services research.…”
Section: Data Collectionmentioning
confidence: 99%
“…The fourth major barrier identi ed was a chronic lack of equipment, medication, and other resources in the facilities, also documented in previous studies in South Africa (2,35,39) and within the Agincourt HDSS study area. (40,41) A 2018 study intervention to improve hypertension care in PHCs in the Agincourt HDSS was unsuccessful, in part due to unreliable blood pressure machines and cuffs, intermittent drug shortages, and lack of space.…”
Section: Discussionmentioning
confidence: 63%
“…(40,41) A 2018 study intervention to improve hypertension care in PHCs in the Agincourt HDSS was unsuccessful, in part due to unreliable blood pressure machines and cuffs, intermittent drug shortages, and lack of space. (40) Mitigating strategies to combat this lack of resources, such as relying on peer-provider networks and drug substitution (39) are not su cient to address the problem of chronic medication shortages. Even when facilities are able to share, providers may often have to use their own money for transport to pick them up.…”
Section: Discussionmentioning
confidence: 99%